DIAGNOSTICS OF THE PRESENCE OF VIRUSES IN THE POTATO AND SOIL - Yin, Zhimin; Michalak, Krystyna (Plant Breeding and Seed Science, 2017)
The paper presents a combined biological assay on indicator plants, a serological assay using ELISA and a molecular assay for detection of viruses that infect the potato. It also elaborates on the bioassay for PVY strain differentiation and for detection of TRV in tubers and soil samples. At IHAR-PIB Młochów Research Center, ELISA tests can be conducted for detection of PVY, PVA, PVM, PVS, PLRV, PVX, TRV and PMTV. Multiplex RT-PCR, real-time quantitative RT-PCR and sequencing methods for detection of PVY, TRV and PMTV are optimized based on a published protocol or developed in our laboratory. The primers for detection of PVY, TRV, PVM, PVS, PLRV, PVX, PMTV, PVA, AMV, CMV, PAMV, TBRV, and BMYV according to the published methods are listed. The maintenance and usage of 19 species of indicator plants are discussed.